Stationary Lactococcus cremoris: Energetic State, Protein Synthesis Without Nitrogen and Their Effect on Survival - Douwenga, Sieze; van Tatenhove-Pel, Rinke J.; Zwering, Emile; Bachmann, Herwig (Frontiers in Microbiology, 2021)
During storage and ripening of fermented foods, Lactococcus cremoris is predominantly in a non-growing state. L. cremoris can become stationary due to starvation or acidification, and its metabolism in these non-growing states affects the fermented product. Available studies on the response of L. cremoris to acid and starvation stress are based on population level data. We here characterized the energetic state and the protein synthesis capacity of stationary L. cremoris cultures at the single cell level. We show that glucose starved stationary cells are energy-depleted, while acid-induced stationary cells are energized and can maintain a pH gradient over their membrane. In the absence of glucose and arginine, a small pH gradient can still be maintained. Subpopulations of stationary cells can synthesize protein without a nitrogen source, and the subpopulation size decreases with increasing stationary phase length. Protein synthesis capacity during starvation only benefits culturability after six days. These results highlight significant differences between glucose starved stationary and acid-induced stationary cells. Furthermore, they show that the physiology of stationary phase L. cremoris cells is multi-facetted and heterogeneous, and the presence of an energy source during stationary phase impacts the cells capacity to adapt to their environment.